Romansa dalam Lintasan Sejarah: Film Habibie & Ainun sebagai Media Edukasi Nilai Nasionalisme dan Inovasi Bangsa - Faidha Mauliya Khasanah; Fahruddin Fahruddin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
The film Habibie & Ainun not only presents a love story of two important national figures but also represents Indonesia’s historical journey through an emotional and inspiring personal narrative. The film combines elements of romance with social, political, and national development contexts, giving it significant potential as a popular medium for historical learning. This study aims to analyze how the film can be utilized as a medium for historical education, particularly in instilling values of nationalism, exemplary leadership, and the spirit of innovation among the wider public, especially the younger generation. This research employs a qualitative approach using narrative analysis to explore visual representations, character dialogues, and storylines that portray B.J. Habibie’s struggle to develop the national technology industry amid political and social dynamics and limited resources. The results indicate that Habibie & Ainun functions as an effective historical learning medium because it successfully connects historical facts with emotional elements that are easily understood and accepted by the public. Through the depiction of the main character’s exemplary qualities, values of dedication, and love for the nation, the film makes a significant contribution to strengthening national identity and enhancing public appreciation of contemporary Indonesian history.